CD4 Count Pattern and Demographic Distribution of Treatment-Naïve HIV Patients in Lagos, Nigeria - Akinsegun Akinbami; Adedoyin Dosunmu; Adewumi Adediran; Sarah Ajibola; Olajumoke Oshinaike; Kikelomo Wright; Olanrewaju Arogundade (AIDS Research and Treatment)
Background. CD4 count measures the degree of immunosuppression in HIV-positive patients. It is also used in deciding when to commence therapy, in staging the disease, and in determining treatment failure. Using the CD4 count, this study aimed at determining the percentage of HIV-positives who require antiretroviral therapy at enrollment in an HIV treatment and care centre. Methods. The Baseline CD4 count, age and gender of 4,042 HAART-naïve patients, who registered between December 2006 and June 2010, at Lagos State University Teaching Hospital, Ikeja, were retrospectively studied. Data were analyzed using SPSS version 16.0 (Statistical Package for Social Sciences, Inc., Chicago, Ill). Results. Patients consisted of 2507 (62%) female and 1535 (38%) males. The mean age of males was years and that of females years. Overall, the mean CD4 count was of cells/mm3. The mean CD4 count of males was cells/mm3 and that of females cells/mm3. A total of 72.3% males, 64.3% females and 67.4% overall registered patients had CD4 count <350 cells/mm3, while only 15.1% males , 20.3% females, and 18.3% overall registered patients had CD4 count >500 cells/mm3 at registration. Conclusion. Females account for more than half of registered patients in HIV clinic and have a relatively higher CD4 count than males. About three-quarter of HIV positives require antiretroviral therapy at registration.